The Association Between Stress Hyperglycemia Ratio (SHR) and Cardiovascular Event in Acute Coronary Syndrome Patients at Adam Malik Hospital - Siregar, Anisafitri; Nasution, Melati Silvanni; Sazli, Brama Ihsan (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2025)
Introduction: Acute hyperglycemia in patients with acute coronary syndrome (ACS) has been associated with major adverse cardiovascular events (MACE). The stress hyperglycemia ratio (SHR) is considered a potential marker for predicting MACE in ACS patients. This study aims to evaluate the relationship between SHR and MACE among ACS patients at Adam Malik Hospital, Medan. Methods: This study employed a retrospective analytic design by collecting data from the medical records of ACS patients treated at Adam Malik Hospital, Medan, during 2022–2023. Inclusion criteria included: confirmed ACS patients (who underwent coronary angiography), while exclusion criteria were: patients with an E-GFR <30 ml/min and those with malignancies, liver diseases, hematological disorders, or infections (sepsis). The chi-square test was used to evaluate the relationship between variables, with a p-value <0.05 considered statistically significant. Results: A total of 100 ACS patients met the study criteria, with an average age of 59 ± 10.3 years, and 78% were male. The mean SHR among the study subjects was 1.09 ± 0.36. MACE was recorded in 64% of patients, including heart failure in 44%, rehospitalization in 12%, stroke in 9%, and mortality in 31%. SHR was found to have a significant relationship with overall MACE (p <0.001) and heart failure events (p = 0.001). However, no association was found between SHR and stroke, rehospitalization, mortality, or 3-point MACE (p >0.05). Conclusion: SHR has a significant relationship with MACE but not with 3-point MACE.